Strategi Penataan Parkir Liar Oleh Dinas Perhubungan Kota Bekasi Di Wilayah Bekasi Selatan - Erika, Pipit; Irwansyah, Iwan (Jurnal Ilmu Administrasi Publik, 2024)
The purpose of this study is to find out how the illegal parking arrangement strategy is by the Bekasi City Transportation Service in the South Bekasi Region, what are the inhibiting factors in implementing the illegal parking arrangement strategy by the Bekasi City Transportation Service in the South Bekasi Region and to find out what the efforts are. taken in implementing the illegal parking management strategy by the Bekasi City Transportation Service in the South Bekasi Region. The type of research used is a qualitative research method with a descriptive research type. Analysis of the data used in the research uses the concept of Henry Mintzberg's strategy scheme to answer the problem formulation. The results of the study show that 1). Plan (program plan and objectives), implementation of patrols for monitoring around city roads as a plan from the transportation service which aims to create smoothness and comfort as well as safety in traffic. 2). Ploy (action plan) by evaluating and patrolling as monitoring and immediately sanctioning violators by locking or ticketing directly by cooperating parties. 3). Position (adaptation to the environment) carry out an evaluation in advance and conduct socialization regarding the importance of orderly traffic. 4). Perspective (point of view) takes action or decisions by making previous observations of certain points that become the point of the problem. 5). Pattern (repeated actions) carrying out routine patrols every week and imposing sanctions such as locking or ticketing violators and carrying out socialization.